PROBLEM-BASED LEARNING MEDIATED BY A DIGITAL PLATFORM: COMPETENCY DEVELOPMENT IN BUSINESS ACCOUNTING EDUCATION - Hernandes, Dayane de Oliveira Pinto Silva; Sousa, Sidinei de Oliveira (Seven Editora, 2026)
This article analyzes, based on a broader research project, how Problem-Based Learning (PBL), mediated by the Be Active digital platform, contributes to the development of students’ competencies in the Business Accounting course of an undergraduate Business Administration program. The study is grounded in the understanding of competencies as the articulation of knowledge, skills, and attitudes, aiming to highlight the formative effects of this proposal in higher education. It is a qualitative and intervention-based study conducted with students from a higher education institution in the interior of the state of São Paulo, Brazil. Data production involved participant observation, document collection, and questionnaires, including the Free Word Association Test, the Kolb Learning Style Inventory, and a questionnaire on PBL. Data were analyzed through triangulation, supported by Similitude Analysis, Discursive Textual Analysis, and Prototypical Analysis. The results indicate that the articulation between PBL and digital mediation fostered the mobilization of knowledge related to course content, the improvement of investigative, communication, and problem-solving skills, as well as the strengthening of attitudes linked to autonomy, responsibility, and collaboration among students. It is concluded that the analyzed experience contributed to a more active and formative learning process in higher education.